Acceptance of virtual reality-based hadith learning model with technology acceptance model (TAM) approach - Hamzah, Muhammad Luthfi; Ansharullah, Ansharullah; Rahmat, Zetri; Zatrahadi, M. Fahli; Purwati, Astri Ayu (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The use of Virtual Reality (VR) technology in education is growing rapidly, including in the context of Islamic learning. This study aims to examine the acceptance of the VR-based Hadith learning model among students of the Islamic Religious Education Study Program of the Riau Islamic University . This study involved a population of 128 students who were active in the 2023/2024 academic year and took Hadith courses. The census method was used for sampling, so that the entire population became the research sample. Data were gathered using a questionnaire designed to assess the study's variables, employing a 5-point Likert scale. The analysis was performed using the Structural Equation Modeling (SEM) technique with the Partial a Squares (PLS) approach. This method was chosen due to its capability to manage intricate models with numerous latent variables and indicators, and its flexibility regarding data distribution assumptions. The results showed that perceived usefulness has a significant positive effect on the intention to use VR for Hadith learning. Meanwhile, Perceived Ease of Use does not have a significant effect on intention to use. These findings indicate the importance of considering the perceived benefits of VR technology in increasing its adoption in the Islamic religious education environment. This research also contributes to the educational literature by emphasizing the importance of technology acceptance and adoption in the context of Islamic religious education.